Opening a window to the acutely injured brain: Simultaneous retinal and cerebral vascular monitoring in rats - Warner, Laura; Bach-Hagemann, Annika; Schmidt, Tobias P.; Pinkernell, Sarah; Schubert, Gerrit A.; Clusmann, Hans; Albanna, Walid; Lindauer, Ute; Conzen-Dilger, Catharina (Frontiers in Molecular Neuroscience, 2023)
Many recent research projects have described typical chronic changes in the retinal vasculature for diverse neurovascular and neurodegenerative disorders such as stroke or Alzheimer's disease. Unlike cerebral vasculature, retinal blood vessels can be assessed non-invasively by retinal vessel analysis. To date, there is only a little information about potential simultaneous reactions of retinal and cerebral vessels in acute neurovascular diseases. The field of applications of retinal assessment could significantly be widened if more information about potential correlations between those two vascular beds and the feasibility of non-invasive retinal vessel analysis in acute neurovascular disease were available. Here, we present our protocol for the simultaneous assessment of retinal and cerebral vessels in an acute setting in anesthetized rats using a non-invasive retinal vessel analyzer and a superficial tissue imaging system for laser speckle contrast analysis via a closed bone window. We describe the experimental set-up in detail, outline the pitfalls of repeated retinal vessel analyses in an experimental set-up of several hours, and address issues that arise from the simultaneous use of two different assessment tools. Finally, we demonstrate the robustness and variability of the reactivity of retinal vessels to hypercapnia at baseline as well as their reproducibility over time using two anesthetic protocols common for neurovascular research. In summary, the procedures described in this protocol allow us to directly compare retinal and cerebral vascular beds and help to substantiate the role of the retina as a “window to the brain.”